A Surgical Robot Teleoperation Framework for Providing Haptic Feedback Incorporating Virtual Environment-Based Guidance - Munawar, Adnan; Fischer, Gregory (Frontiers in Robotics and AI, 2016)
In robot-assisted teleoperated laparoscopic surgeries, the patient side manipulators are controlled via the master manipulators, operated by the surgeon. The current generation of robots approved for laparoscopic surgery lack haptic feedback. In theory, haptic feedback could enhance the surgical procedures by providing a palpable sense of the environment as a function of surgeon’s hands movements. This research presents an overall control framework for haptic feedback on existing robot platforms and demonstrates on the daVinci Research Kit. Toward this end, the paper discusses the implementation of a flexible framework that incorporates stiffness control with gravity compensation for the surgeon manipulator(s). This is coupled with a sensing and collision detection algorithm for calculating the interaction between the slave manipulators and the surgical area.